eBay Hacks - Karp, David A. (O'Reilly, 2011)
Whether you're a newcomer or longtime user, eBay Hacks will teach you to become efficient as both a buyer and seller. You'll find a wide range of topics, from monitoring the bidding process, getting refunds, and fixing photos so that sale items look their best, to in-depth tips for running a business on eBay and writing scripts that automate some of the most tedious tasks. The book also gives you an inside look into the unique eBay community, where millions of people gather online to buy and sell. Author David Karp--an eBay user from the very beginning--teaches you how to work within this community to maximize your success.